Working from Home during the COVID-19 Pandemic: What is the Impact on Employees’ Psychological Meaningfulness, Safety and Availability? - Daulay, Siti Fani; Mustika, Martina Dwi (Bina Nusantara University, 2021)
The research aimed to explore the relation of work-home and home-work interactions on employees’ psychological condition while working from home during the COVID-19 pandemic. The coronavirus (COVID-19) pandemic had led various organizations to implement work-from-home measures. This rapid change in working arrangements might affect employees’ psychological condition as they navigate both their work and home responsibilities at the same time and place. The research involved 2.288 employees at one government institution in Indonesia. Data were collected in April 2020, using the web-based tool Survey Monkey. The data were analyzed by logistic regression analysis. The results show that Negative Work–Home Interactions (NWHI) are significantly associated with psychological meaningfulness and psychological safety, while Negative Home–Work Interactions (NHWI) are significantly associated with the three psychological dimensions. Positive Work–Home Interactions (PWHI) are significantly associated with psychological safety, while Positive Home–Work Interactions (PHWI) are significantly associated with the three psychological dimensions. Based on the results, it can be concluded that positive and negative experience that happens at work spill over to the home domain and vice versa, which could, in turn, impact on employee sense of meaningful, safety, and sense of having the physical, emotional, and psychological resources to perform tasks at work during working from home. Therefore, organizational support is important in maintaining employees’ psychological condition while working from home during the pandemic.